Extraction and Optimization of Active Metabolites From Cluster Bean: An In Vitro Biological and Phytochemical Investigation. Issue 2 (6th May 2022) - Riaz, Saima; Hussain, Iqbal; Ibrahim, Muhammad; Ishtiaq, Muhmmad; Ali, Qasim; Muazzam Ali, Muhammad; Sajid Hamid Akash, Muhammad
The current study aimed to explore active metabolites of locally recognized and high yielding cultivar cluster bean (BR-99) with a wide range of adaptability having antioxidant, antidiabetic, antimicrobial, and cytotoxic potential. Six solvents were used (crude methanol, n-hexane, chloroform, ethyl acetate, butanol, and aqueous) with escalating polarity for colorimetric determination of antioxidants such as total phenolic contents (TPC), total flavonoid contents (TFC), and free radical scavenging activity (FRSA) by DPPH (2, 2-diphenyl-1-picrylhydrazyl) assay. Moreover, an antidiabetic and anticancer study was conducted by α-amylase inhibition and MTT (3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-tetrazolium bromide) assay. Biological investigations were carried out against the most commonly found infectious microbial strains. The significant results (P ≤ .001) of each activity were seen among six tested solvent extracts. The ethyl acetate and methanol extract have more antioxidant potential with the highest TPC (16.38 ± .13 mg GAE/g) and TFC (8.15 ± .24 mg CE/g), respectively. Similarly, methanol extract presented the highest free radical scavenging activity (46.31 ± .91%), followed by ethyl acetate, butanol, chloroform, aqueous, and n-hexane extract. However, the maximum α-amylase inhibition (62.54 ± 1.47%) and anticancer activity against human lung cancer cells were congregated (78.31 ± 1.46%) in butanol and chloroform, respectively. A positive correlation was seen between TPC with TFC ( R 2 = .8356), FRSA ( R 2 = .8381), and anti-diabetic activity ( R 2 = .8082), which highlights the phenolic contents as strong anti-oxidant agents especially flavonoids. Each extract of cluster bean (BR-99) showed significant antimicrobial activities for all tested bacterial strains except B. cereus and E. coli . The profound results of maximum antibacterial activity were witnessed by chloroform extract while ethyl acetate extracts showed great antifungal potential against all tested fungal strains. The HPLC quantitative analysis results of cluster bean (BR-99) revealed the presence of active phytochemicals such as gallic acid, HB acid, vanillic acid, kaempferol, sinapic acid, ferulic acid, salicylic acid, coumarins, quercetin, rutin, p-coumaric acid, and catechin, and the variation in both phytochemical and biological spectrums envisioned the cluster bean (BR-99) used in future as a cheap, safer, and potent source of bioactive drugs.